Declining assistance to developing-country agriculture: change of paradigm? - Dresrüsse, Günter (International Food Policy Research Institute, 1995)
Is the agricultural sector in developing countries now facing the same neglect that it did in industrial countries some 200 years ago? This concern arises because agricultural investments are declining and donors are paying scant attention to agriculture in their development strategies. Is the neglect of agriculture a one-way trend or is it a cyclical issue? Or is it simply a symptom that can be quickly remedied by new policy orientations? An important step in examining this issue is to identify phases in the macroeconomic and political thinking that have guided the actions of those concerned with developing countries since the 1950s. By the year 2020, an additional 2.8 billion people will have to be nourished. Since the potential for land expansion is limited, the necessary food production increases will have to be generated by productivity increases and technical progress. Will research and development be able to provide technology to areas where production increases must be achieved without destroying the resource base? Will there be enough financial and technical input to activate this necessary second Green Revolution? The author explores the dilemma, the causes, and suggests a changed paradigm.